2000
DOI: 10.1021/jm990550b
|View full text |Cite
|
Sign up to set email alerts
|

2-Substituted Tryptamines:  Agents with Selectivity for 5-HT6Serotonin Receptors

Abstract: Several 2-alkyl-5-methoxytryptamine analogues were designed and prepared as potential 5-HT(6) serotonin agonists. It was found that 5-HT(6) receptors accommodate small alkyl substituents at the indole 2-position and that the resulting compounds can bind with affinities comparable to that of serotonin. In particular, 2-ethyl-5-methoxy-N, N-dimethyltryptamine (8) binds with high affinity at human 5-HT(6) receptors (K(i) = 16 nM) relative to 5-HT (K(i) = 75 nM) and was a full agonist, at least as potent (8: K(act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 17 publications
(39 reference statements)
2
109
0
1
Order By: Relevance
“…In addition, 2-Me-5-HT has affinity for 5-HT 6 Rs [38] and consequently as described above we tested the antiemetic potentials of its corresponding antagonists (Ro-046790 [39] and Ro4368554 [40]) against the induced emesis. At doses 0.25, 1, 5, 10, and 20 mg/kg (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 2-Me-5-HT has affinity for 5-HT 6 Rs [38] and consequently as described above we tested the antiemetic potentials of its corresponding antagonists (Ro-046790 [39] and Ro4368554 [40]) against the induced emesis. At doses 0.25, 1, 5, 10, and 20 mg/kg (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…GF-62 cells, a stable cell line expressing the 5-HT 2A receptor (8), was used for functional studies of 5-HT 2A receptors. All other receptors were obtained as previously described (9,10) as part of the National Institute of Mental Health Psychoactive Drug Screening Program (NIMH-PDSP) resource.…”
Section: Methodsmentioning
confidence: 99%
“…Radioligand-Binding Assays. Radioligand-binding assays at human cloned GPCRs, ion channels, and transporters were performed as previously detailed (9,10) by using the resources of the NIMH-PDSP. Detailed on-line protocols are available for all assays at the NIMH-PDSP web site (http:͞͞pdsp.cwru.edu).…”
Section: Methodsmentioning
confidence: 99%
“…2 nM) as one of the first examples of a 5-HT 6 receptor antagonist. 7,8 Subsequent pharmacophoric studies have revealed that the 5-methoxy group of 1a is not required for binding (i.e., 1b; K i = 4 nM), that the benzenesulfonyl moiety can be replaced by a benzyl group (2; K i = 6 nM) with retention of antagonist action, 5 and that the indole N 1 nitrogen atom is not required for binding, as evidenced by the high affinity of, for example, isotryptamine 3 (K i = 32 nM) and indene 4 (K i = 3 nM) for this receptor population. 9 Various tryptamines lacking an N 1 substituent generally bind with reduced affinity and, like 5-hydroxytryptamine (i.e., serotonin; K i ca.…”
Section: -Htmentioning
confidence: 99%